Crystal-Chemistry of Point Defects and Mechanisms Formation of Solid Solutions CdxZn1-xTe - Gurgula, G.Ya.; Vintonyak, T.P.; Yaremiychuk, O.V. (Physics and Chemistry of Solid State, 2015)
A Crystal-formulas defined dominant point defects in solid solutions CdxZn1-x Te for n-and p-type conductivity output binary compounds ZnS and ZnTe. Dependence of the concentration of defects, free carriers and Hall concentration on the composition of the solid solutions.